Bringing behavioral observation of couples into the 21st century - Bulling, Lisanne J; Heyman, Richard E; Bodenmann, Guy (Journal of family psychology, 2023)
Recent technological advances have made the remote recording of interactions and the automatic extraction of nonverbal, paraverbal, and verbal behavioral cues from the videos possible. The development of computer programs that can replace human observational coders is imminent. The increasing availability of such new technologies, accompanied by their lower costs and greater convenience, is likely to advance behavioral observation research, giving new insight into the fine-grained moment-to-moment interactional processes. We illustrate how couple researchers can use recent technological advances to bring behavioral observation research into the 21st century. (PsycInfo Database Record (c) 2023 APA, all rights reserved).